Designing motivator static forms to prevent risk disease: consideration for graphic designers / Muhammad Nur Firdaus Nasir … [et al.] - Nasir, Muhammad Nur Firdaus; Abd Rahim, Ruslan; Harun, Azahar; Mohamad Khalil, Musaddiq (Universiti Teknologi MARA, Kedah, 2020)
Prevention of the disease can only be succeed if the message can be deliver to target audience and they willing to perform health behavior to prevent from risk disease. The purpose of this article was to review the literature about framework that could be a motivator for target audience to change their behavior and also to maximize their effectiveness. Future recommendations also will be added in this paper in order to enhance the framework. Literature review of published research and education articles. The needs of few features that can complete the framework in order to help the target audience to perform behavior change is required. In order to be effective, McGuire’s conceptual framework need to hybrid with Fobb’s behavior model to analyze outcome for behavior change among target audience. Graphic designer need to identify the use of static form that could motivate target audience to perform health desirable behavior in order to prevent them from risk disease. The use of image might be vary and need to be acceptable to range of age target audience.